GREEN INVESTMENTS: THE EXPERIENCE OF DEVELOPING COUNTRIES (American Journal of Pedagogical and Educational Research, 2025)
In the context of a deepening ecological crisis, green investments have become an integral component of sustainable economic development. The experience of developing countries is particularly relevant, as investments in environmental projects can simultaneously stimulate economic growth, improve social indicators, and reduce environmental degradation. This article examines the theoretical foundations of green investments, their role in building a sustainable economy, and analyzes green investment project implementation across Asia, Africa, and Latin America. Special attention is paid to financing mechanisms, public-private partnerships, and international support.